2006
DOI: 10.1083/jcb.200510065
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-mediated clearance of huntingtin aggregates triggered by the insulin-signaling pathway

Abstract: Conditional mouse models of polyglutamine diseases, such as Huntington's disease (HD), have revealed that cells can clear accumulated pathogenic proteins if the continuous production of the mutant transgene is halted. Invariably, the clearance of the protein leads to regression of the disease symptoms in mice. In light of these findings, it is critical to determine the pathway responsible for alleviating this protein accumulation to define targets to fight these diseases. In a functional genetic screen of HD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
287
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(303 citation statements)
references
References 69 publications
12
287
2
Order By: Relevance
“…In contrast, insulin receptor substrate (IRS)-2, which activates PI-3K/Akt and mTOR cascade, promoted mitochondrial dysfunction and oxidative stress in R6/2 mice; however, in the same study, the authors showed that IRS-2 protein levels were unchanged in the striatum of patients with grade II HD [80]. Conversely, IRS-2 activation induced by insulin, IGF-1 and interleukin-4 enhanced exon1Htt clearance in a dosedependent manner [81]. Thus, different IRS signaling pathways might be activated upon exposure to low nM insulin or IGF-1.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, insulin receptor substrate (IRS)-2, which activates PI-3K/Akt and mTOR cascade, promoted mitochondrial dysfunction and oxidative stress in R6/2 mice; however, in the same study, the authors showed that IRS-2 protein levels were unchanged in the striatum of patients with grade II HD [80]. Conversely, IRS-2 activation induced by insulin, IGF-1 and interleukin-4 enhanced exon1Htt clearance in a dosedependent manner [81]. Thus, different IRS signaling pathways might be activated upon exposure to low nM insulin or IGF-1.…”
Section: Discussionmentioning
confidence: 91%
“…A reduction of levels of Beclin1 leads to the accumulation of mHtt and reduced the viability of animals in a mouse model of HD 156 . The autophagic response initiated by the exposure of cultured cells to Aß is mediated by PI3K 157 , and a similar induction of autophagy through PI3K occurs in cell culture models of HD 158 . On the other hand, blocking autophagy through the pharmacological inhibition of PI3K by 3-methyladenine increases the levels of mHtt and reduces viability 159 .…”
Section: Targeting the Pi3 Kinase And Beclin Pathwaymentioning
confidence: 89%
“…Reduced BDNF levels 39,40 Increasing BDNF & NGF levels is beneficial in disease models [51][52][53][54] Increased p75 NTR levels and signalling 75,172 Decreased Trk receptor levels and signalling 75,172 Increased Gsk3ß activity 66,173 Altered ERK activity 174 Reduced velocity and efficiency of axonal transport of BDNF 65,66 Apoptotic pathways Increased caspase-6 activity 89,90 Caspase-6 cleavage of disease proteins [89][90][91][92] Preventing caspase cleavage of disease proteins is beneficial in mouse models 93,94 Posttranslational modifications Palmitoylation of disease proteins is linked to aggregate formation 118,119 Phosphorylation of disease proteins reduces their cleavage by caspases 105,106 HDAC inhibition is beneficial in disease models 69,126,127 Protein aggregation and clearance mechanisms Misfolding and aggregation of disease proteins 128 UPS impairment 144,145 Impaired autophagy 161 Upregulation of autophagy is beneficial in disease models 153,155,156,158,162,163,165,167,<...>…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The combined use of GEP and RNAi technology has been demonstrated to be a valuable strategy to validate potential drug targets (33)(34)(35), and RNAi has been recently used to efficiently probe the gene function on a whole-genome scale in mammalian cells (36,37). Here, ALK transcriptional targets were validated through a small-scale genetic screening, using lentiviral shRNA sequences.…”
Section: Discussionmentioning
confidence: 99%